Experiences and socio-environmental contexts in the lead-up to psychosis: a qualitative analysis of the narratives of persons with psychosis from different ethnic, racial and immigrant backgrounds - Xavier, Salomé M.; Both, Adrianne; van der Ven, Els; Ferrari, Manuela; Abdel-Baki, Amal; van den Bogerd, Nicole; Lemmers-Jansen, Imke; Iyer, Srividya N. (Frontiers in Psychiatry, 2025)
IntroductionPrevious research, predominantly quantitative, has attributed the excess risk for psychosis among immigrants and ethnic minorities to social adversity, discrimination and structural inequities. Although calls have acknowledged their potential for yielding nuanced insights, qualitative methods focused on first-person narratives have not been used in research into the social determinants of the development of psychosis.MethodsWe explored the experiences and socio-environmental contexts of individuals with psychosis from diverse ethno-racial and immigrant backgrounds. We also gathered their perspectives on the causality of psychosis. We conducted in-depth interviews with 24 participants at early intervention services for psychosis in Montreal, Canada.ResultsThrough thematic analysis, we identified five themes: “Spaces and societies of oppression”; “Nothing to hold on to”; “Mistreated, invisible or seen in the wrong light”; “Places of freedom, connection and safety”; and “Healing and well-being”. Spaces described as oppressive fomented experiences of precarity, isolation and mistreatment. Spaces of freedom, connection and inclusivity enabled healing and well-being. Experiences of precarity, mistreatment and exclusion were more frequent for minoritized individuals. Participants attributed psychosis to multiple factors, many pertaining to social contexts.DiscussionOur findings shed light on the processes through which social contexts shape the lives and illness development of individuals from diverse backgrounds. By framing them within particular life stories and places, we gain a fuller, more fine-grained understanding of the social-structural determinants that have been identified in quantitative studies. Our work highlights the need to attend closely to patients’ social contexts and narratives and advocate for inclusivity, equity, and connection at the societal level.